Adaptação transcultural e propriedades psicométricas do “Occupational Self Assessment” para a língua portuguesa do Brasil - Mendes, Paulo Vinicius Braga (2020)
Introduction: The instrument “Occupational Self Assessment v.2.2” (OSA) is based on the Model of Human Occupation. This instrument measures the constructs of occupational competence and values attributed to activities, according to the person's perceptions, assisting in the development of therapeutic objectives according to the client-centered practice. In Brazil, there are few standardized occupational therapy instruments for use. Thus, research points to the need for cross-cultural adaptation and assessment of the psychometric properties of instruments for use in the Brazilian context. Objectives: the objectives were to carry out cross-cultural adaptation, test reliability and examine the construct validity of the “Occupational Self Assessment v.2.2” instrument for Brazilian Portuguese. Materials and Methods: the cross-cultural adaptation was based on two international guides: 1) Guidelines for the Process of Cross-Cultural Adaptation of Self-Report e 2) Report of the ISPOR Task Force for Translation and Cultural Adaptation. Through the following steps: 1) Preparation, 2) Translation, 3) Translation Synthesis, 4) Back-translation, 5) Expert Committee Review, composed of ten professionals, among them occupational therapists, translators and back-translators and a physiotherapist and finally, 6) Pre-test, composed of 24 subjects divided into two groups: twelve people with disabilities and twelve undergraduate students in occupational therapy. The reliability and construct validity tests were performed using a sample of forty (n = 40) participants with physical disabilities who responded to the OSA at two different times, within an interval of ten to fourteen days from the first administration, to assess the test-retest reliability. The interclass correlation test was used as a statistical method to verify the reproducibility of the instrument. For the internal consistency test, Cronbach's alpha coefficient was calculated. The SF-36 instrument was applied to test the construct validity of the Brazilian version of OSA. Finally, to identify relationships between occupational competence and values measured by the OSA, the instruments Functional Independence Measure (FIM) (for the variable of functional independence level), the User Satisfaction Assessment with Quebec Assistive Technology - QUEST (for the variable of satisfaction with technology) and SF-36 (for variable of quality of life ); which were analyzed by Spearman's correlation coefficient. Results: After the stages of translation, back-translation, the committee of experts presented between 90-100% of agreement regarding the equivalences of the instrument in the Brazilian Portuguese version. The Brazilian version of the OSA obtained satisfactory indices for reliability, with an index of 0.84 for the evaluation of occupational competence and 0.82 for the evaluation of the values of the questionnaire "OSA - BR – Myself", 0.77 for the evaluation of competence occupational and 0.89 for the values of the questionnaire “OSA - BR – My Environment”, in the inter-class correlation test to assess the stability of the instrument. For the evaluation of internal consistency, the Brazilian version of OSA - BR obtained an index of 0.86 for the assessment of occupational competence and 0.88 for the evaluation of the values in the questionnaire "OSA - BR - Myself", also obtained 0.73 in the evaluation of occupational competence and 0.85 in the evaluation of the values in the questionnaire "OSA - BR – My Environment". The assessment of occupational competence of the questionnaire "OSA - BR - Eu Myself" has a significant correlation with the SF-36 instrument, showing a correlation with the domains "Limitation due to physical aspects (p = 0.001 / 0.506)," General health status "( p = 0.01 / 0.394), “Vitality” (p = 0.002 / 0.470), “Social aspects” (p = 0.003 / 0.454), “Limitations due to emotional aspects” (p = 0.02 / 0.367) and “Health Mental ”(p = 0.001 / 0.490), also presents a significant correlation (p = 0.006 / 0.423) between the occupational competence assessment of the“ OSA - BR – My Environment” questionnaire and the SF-36 domain of “Mental Health”, which demonstrates its construct validity. A significant correlation was found between the occupational competence of the “OSA-BR - Eu Myself” scale and the FIM (p = 0.02 / 0.364). There was no significant correlation between this scale and QUEST. Conclusion: The instrument has been translated and has good psychometric properties for use in Brazil with people with physical disabilities. Through the methodology adopted in this study, it was possible to give rise to the instrument "Occupational Self-Assessment - Brazil".